ASSA13-03-35 Establishment and Identification of Stable Cell Line HEK293/BKCA in Molecular and Electrophysiological Levels. (29th April 2013) - Rui, Zhou; Wenjun, Huang; Liang, Mao; Tao, Li; Jing, Wen; Yan, Yang; Xiaorong, Zeng
Abstract : Objective: Large conductance Ca 2+ -sensitive K + channels (BKCa ) are involved in dysfunctional relaxation of artery in patients with hypertension and represent an attractive target for drug discovery. In this study, we aimed to establish the stable cell line HEK293/BKCa as a future in-vitro drug-screening platform. Methods: HEK293 cell with stable expression of BKCa was constructed through transfecting the plasmid pcDNA3.1-BKCa . Molecular and electrophysiological characteristic of HEK293/BKCa were identified by molecular biology and patch clamp techniques. Results: Semiquantitative RT-PCR and Western blot showed that BKCa was highly expressed in HEK293/BKCa while not in control cells. Using Immunofluorescence method, strong positive fluorescence signal for BKCa was observed specifically in membrane of BKCa cells. Single-channel patch clamp experiments showed that the open probability of BKCa in the cell was voltage and calcium dependent. In insideout configuration, The Am and N Po of single-channel in HEK293/BKCa gradually enhanced with the increased voltage (0, 10, 20, 30, 40, 50, 60 mV). Moreover, The Am and N Po also showed Increasing tendency with increased calcium concentration (0, 122, 187 nM) at a certain voltage. External applied IBTX (BKCa specific antagonist) led to complete inhibition in channel activity. Conclusions: Taken together, these results indicated that HEK293/BKCa stable cell line was successfully constructed and BKCa channel expressed in HEK293 cells exhibited functional features similar to native BKCa channels. Which would serve as an efficient tool for future drug-screening targeted BKCa .